Do oil price fluctuations affect the inflation rate in Indonesia asymmetrically? - Lim, Thye Goh; Siong, Hook Law; Trinugroho, Irwan (World Scientific Publishing, 2020)
Changes in the oil price directly affect production costs, and subsequently, the general price level of products. With Indonesia observing an inflation targeting policy, this study applies the nonlinear autoregressive distributed lag (NARDL) technique to investigate the effect of oil price fluctuations in Indonesia. The relationship is important for the central bank to gauge the effectiveness of the inflation targeting policy in immunizing the country from oil price fluctuations. Our findings have revealed that there was an asymmetric behavior between oil price and the inflation rate (producer price index), thus questioning the effectiveness of the inflation targeting policy. More specifically, in the long run, an increase in the oil price will tend to lead to an increase in the rate of inflation with a greater deviation, while an oil price reduction will lead to a decrease in the inflation rate with a lower deviation. This suggests that the benefits of an oil price reduction are not passed down to the consumer.